Masculinization in Parents of Offspring With Autism Spectrum Disorders Could Be Involved in Comorbid ADHD Symptoms. (September 2017) - Romero-Martínez, Ángel; Polderman, Tinca J.C.; González-Bono, Esperanza; Moya-Albiol, Luis
Objective: People with autism spectrum disorders (ASD) often have comorbid ADHD symptoms. ASD and ADHD are both associated with high intrauterine testosterone (T) levels. This study aims to investigate whether masculinization predicts inattention symptoms in parents, and in their ASD-affected offspring.Method: The sample consisted of 32 parents with ASD-affected children (13 male, 19 female) and 32 offspring individuals (28 male, 4 female). Masculinization of parents was measured by 2D:4D finger ratio, and current T levels. Inattention in both parents and in their offspring was measured with behavior questionnaires.Results: The results indicated that masculinized 2D:4D explains inattentive ADHD symptoms in ASD parents and in their offspring. These predictions are mediated by T and inattention symptoms of ASD parents, respectively.Conclusion: These findings suggest the existence of a masculinized endophenotype in ASD parents, which may be characterized by high attentional sensitivity to T effects.